Serum galectin‐3 level as a marker of thrombogenicity in atrial fibrillation. Issue 6 (13th March 2017) - Kocyigit, Duygu; Gurses, Kadri Murat; Yalcin, Muhammed Ulvi; Canpinar, Hande; Canpolat, Ugur; Evranos, Banu; Yorgun, Hikmet; Ozer, Necla; Guc, Dicle; Aytemir, Kudret
Abstract : Background: Left atrial appendage flow velocity (LAAFV) and presence of spontaneous echo contrast (SEC) have been reported to be predictors of thromboembolism in atrial fibrillation (AF) patients. Galectin‐3 is a biomarker reflecting pro‐inflammatory status, whose role in AF has recently drawn attention, particularly in persistent AF population. Aim: In this study we aimed to investigate the association between serum galectin‐3 levels and echocardiographic predictors of thromboembolism in persistent AF patients. Methods: We included 65 persistent AF patients (55.50±10.67 years, 46.15% male). Transesophageal echocardiography (TEE) was performed to assess LAAFV and presence of left atrial (LA)/LA appendage (LAA)‐located SEC and thrombus prior to direct current cardioversion or catheter ablation for AF. Results: Median galectin‐3 level was 0.63 ng/mL. Serum galectin‐3 levels were significantly correlated with LAAFV ( r =−.440, P <.001). Serum galectin‐3 levels were associated with presence of SEC ( P <.001), and LA thrombus ( P =.008). Receiver operating characteristic analysis revealed that a serum galectin‐3 greater or equal to the cut‐off value of 0.69 predicted presence of SEC with a sensitivity and specificity of 91.00% and 79.00%, respectively ( P <.001). Conclusion: In conclusion, in the setting of persistent AF, serum galectin‐3 levels are associated with presence of SEC and LAAFV on TEE. Our findings suggest that serum galectin‐3 level may have a place in thromboembolism risk stratification in persistent AF patients.